Statins and skeletal muscles toxicity: From clinical trials to everyday practice - Norata, Giuseppe; Tibolla, G.; Catapano, A. (Academic Press, 2014)
The mechanism(s) underlying the occurrence of statin-induced myopathy are ill defined, but the results of observational studies and clinical trials provide compelling evidence that skeletal muscle toxicity is a frequent, dose-dependent, adverse event associated with all statins. It has been suggested that reduced availability of metabolites produced by the mevalonate pathway rather than intracellular cholesterol lowering per se might be the primary trigger of toxicity, however other alternative explanations have gained credibility in recent years. Aim of this review is: (i) to describe the molecular mechanisms associated to statin induced myopathy including defects in isoprenoids synthesis followed by altered prenylation of small GTPase, such as Ras and Rab proteins; (ii) to present the emerging aspects on pharmacogenetics, including CYP3A4, OATP1B1 and glycine amidinotransferase (GATM) polymorphisms impacting either statin bioavailability or creatine synthesis; (iii) to summarize the available epidemiological evidences; and (iii) to discuss the concep ts that would be of interest to the clinicians for the daily management of patients with statin induced myopathy. The interplay between drug-environment and drug-drug interaction in the context of different genetic settings contribute to statins and skeletal muscles toxicity. Until specific assays/algorithms able to combine genetic scores with drug-drug-environment interaction to identify patients at risk of myopathies will become available, clinicians should continue to monitor carefully patients on polytherapy which include statins and be ready to reconsider dose, statin or switching to alternative treatments. The beneficial effects of adding agents to provide the muscle with the metabolites, such as CoQ10, affected by statin treatment will also be addressed. © 2014 Elsevier Ltd.